Phonological differences between syndromes with neurodevelopmental disorders: evidences from the most frequent phonological processes - Hidalgo de la Guía, Irene; Garayzábal Heinze, Elena (Revista de Investigación en Logopedia, 2019)
Neurodevelopmental disorders present in different genetic disorders such as Down syndrome, Williams syndrome and Smith Magenis syndrome underlie the cognitive, behavioral and linguistic characteristics of people who suffer from them. Despite theses three genetic disorders have phenotype aspects in common, like intellectual disability, studies show that each syndrome has different linguistic profiles. Regarding the phonetic and phonological abilities of people with these three syndromes, peculiarities have been identified related to the way they develop their phonology. That might mean certain specificity of some phonological patterns for each syndrome. A prolix description about these phonic profiles implies an advance in the speech assessment process and an improvement in the effectiveness of speech therapy by the design of specific therapy tools for the linguistic conditions of each alteration. Thus, the speech of three groups of children, teenagers and adults with Down syndrome (DS), Williams syndrome (WS) and Smith Magenis syndrome (SMS) has been evaluated. The first one consists of 13 cases, the second group with SW is made up of 15 cases and the group with SMS is formed by 21 participants. The speech analysis has been carried out from the productive level by tasks of naming, repetition and spontaneous speech samples. The results represent significant findings that allow us to deepen the most active phonological processes in each of these three populations with intellectual disabilities. These findings highlight that it is necessary a thorough description of the specific linguistic profiles for each disease with neurodevelopmental disorders.
Keywords: Down syndrome; Williams syndrome; Smith Magenis syndrome; phonological processes; phonetic and phonological profile